PELATIHAN PEMBUKUAN UNTUK UMKN (USAHA MIKRO KECIL DAN MENENGAH ) DI DUSUN SUNGAI ARANG KECAMATAN BUNGO DANI KABUPATEN BUNGO - Ferdian, Tommy (EDUTECH CONSULTANT, 2019)
Community service aims to make UMKN (Micro, Small and Medium Enterprises) in Sungai Arang Hamlet, Bungo Dani District, Bungo Regency able to make their own books so that they are orderly in carrying out their financial records so that their expenses and income can be measured and profits obtained. The target of service is UMKN (Micro, Small and Medium Enterprises) located in Sungai Arang Hamlet, Bungo Dani District, Bungo Regency. Preparations were made with a survey to see the conditions in the field regarding the accounting for MSMEs (Micro, Small and Medium Enterprises). The implementation was carried out by training methods with the presentation method followed by question and answer discussions and case studies Results of bookkeeping training activities for MSMEs (Micro, Small and Medium Enterprises) in Sungai Arang Hamlet Bungo Dani District, Bungo District This financial accounting training showed a positive response from actors or trainees so that training participants can understand and improve the skills and knowledge of business people, can separate personal finance from businesses, and business people can know the development of their business through good accounting.